Accessibility to services of general interest in polycentric urban system planning: the case of Portugal. Issue 6 (2nd June 2020) - Sá Marques, Teresa; Saraiva, Miguel; Ribeiro, Diogo; Amante, Ana; Silva, Duarte; Melo, Paulo
ABSTRACT: Today, major planning agendas in Europe steer the future of territorial organization towards an urban polycentric perspective. The accessibility to services of general interest (SGI), a significant source of spatial inequality in Europe, is one of the key challenges to address. However, instruments needed to support the implementation and monitoring of territorial policy measures regarding the distribution of, and accessibility to SGI are still under-developed. Studies generally relate to the (intra)regional and not the national scale. When they do so, they lose local specificity as they often consider the existence/availability of services at a given scale and not the actual capacity to reach their (often just estimated) location through the transport network. In the context of the revision of Portugal's National Plan for Territorial Planning Policies, this paper presents a comprehensive multi-criteria location-based approach for measuring the factual accessibility to a representative range of SGI at the national Portuguese scale. Results are evaluated considering the dichotomy between centrality and periphery, high and low density, and the regional disparities found. High accessibility values do not necessarily mean greater territorial cohesion. Contributions to the development of national planning policies that respond to cohesion challenges are also debated.